2017
DOI: 10.17533/udea.rccp.v30n3a04
|View full text |Cite
|
Sign up to set email alerts
|

Magnetized drinking water improves productivity and blood parameters in geese

Abstract: El agua de bebida magnetizada mejora la productividad y los parámetros sanguíneos en gansos A água magnetizada melhora a produtividade e os parâmetros sanguíneos em gansos AbstractBackground: Quality of drinking water is an issue that imposes limits on animal farming. Improving water quality can be a solution to animal farming and to the enhancement of animal production in areas with limited water supplies. Objective: To evaluate the eff ect of water quality and magnetized water on productivity and blood para… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 10 publications
1
11
0
Order By: Relevance
“…The recovery of water physic-chemical quality by water passing through a magnetic field acquires a finer and more homogeneous structure (17), reduces the hydrogen-oxygen bond angle within the water molecule (5), due increase in water consumption 79.22 ml/bird in the group 0.2 T MTW that led up to improvement in overall quail hens reproductive performance: egg production up to 92.58%, egg weight 13.25 g, and estrogen hormone concentration which increases water fluidity and ability to dissolve various constituents such as minerals and vitamins (18), leading to better water absorption across cell membranes. The recent results with the results of El-Hanoun et al (10) exalted magnetic treatment of tap and well water improved water consumption, productive performance, such as number, weight and mass of eggs, feed conversion ratio of geese compared with groups without magnetically treated. For the same reasons above the male performance presented of ejaculate volume, sperm concentration, individual and mass motility, live and normal morphology sperm percentages, semen quality factor, quantity of foam and testosterone hormone concentration increased.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…The recovery of water physic-chemical quality by water passing through a magnetic field acquires a finer and more homogeneous structure (17), reduces the hydrogen-oxygen bond angle within the water molecule (5), due increase in water consumption 79.22 ml/bird in the group 0.2 T MTW that led up to improvement in overall quail hens reproductive performance: egg production up to 92.58%, egg weight 13.25 g, and estrogen hormone concentration which increases water fluidity and ability to dissolve various constituents such as minerals and vitamins (18), leading to better water absorption across cell membranes. The recent results with the results of El-Hanoun et al (10) exalted magnetic treatment of tap and well water improved water consumption, productive performance, such as number, weight and mass of eggs, feed conversion ratio of geese compared with groups without magnetically treated. For the same reasons above the male performance presented of ejaculate volume, sperm concentration, individual and mass motility, live and normal morphology sperm percentages, semen quality factor, quantity of foam and testosterone hormone concentration increased.…”
Section: Discussionmentioning
confidence: 56%
“…Dramatically improvement of broiler breeder performance by producing more eggs, egg weight, hatchability, immunity, physiology and microbiological so survived longer when used magnetized water (9). Magnetized well water improved body weight and feed conversion rate of birds, besides renal and hepatic functions; it also increased production, quality and hatchability of eggs, levels of reproductive hormones (progesterone and estrogen), and the blood antioxidant status (10).…”
Section: Introductionmentioning
confidence: 99%
“…The body weight increases with age of domestic geese [ 18 ]. The Embden Goose had heavier carcass weight than Toulouse and its cross groups [ 19 ] and Egyptian Geese [ 20 , 21 ]. The Embden breed has a heavy body weight and faster gain weight.…”
Section: Discussionmentioning
confidence: 99%
“…The improvement obtained with magnetic water in the present study for Japanese quail is in agreement with Al-Fadul (2006) who reported that magnetization of the water significantly increased Arbor Acres broiler LBW especially in the late weeks. The ingestion of magnetized tap water improved body weight (El-Hanoun et al, 2017).…”
Section: Live Body Weight (Lbw)mentioning
confidence: 95%